A low voltage ride-through strategy for grid-connected PV converters based on variable power point tracking method. (November 2022) - Li, Tiecheng; Fan, Hui; Zeng, Siming; Hu, Xuekai; Meng, Zhengji; Zhao, Yuhao
Abstract: A novel low voltage ride through control strategy with variable power tracking trajectory is proposed. The voltage fall amplitude is controlled by feedforward, and the tracking trajectory of power point is adjusted to realize the real-time change of the photoelectric cell voltage. On this basis, the output power of the photovoltaic generation system is controlled quickly and efficiently, and the purpose of power balance in the PV inverter is achieved. Through collaborative control of the grid-tied inverters, the output current of grid-tied inverter can meet the active and reactive power requirements of power grid as much as possible without overing the limit. In this way, the maximized support for the voltage recovery of power grid which contains zero voltage ride through is realized. In the non-standard environment, the proposed control strategy is proven to be effective by the simulation results. Compared with traditional LVRT strategy, the proposed strategy in this paper not only realizes the safe and reliable operation, but also improves the economy of photovoltaic power generation system, without any add additional equipment.